Occurrence of Pharmaceuticals and Personal Care Products in Cannabis sativa L. Following Application of Sewage Sludge-Based Composts and Vermicomposts - Ales Hanc; Bayu Dume; Sarka Kusnierova; Milan Hrcka; Tereza Hrebeckova; Pavel Michal; Maha Hleibieh; Alena Nehasilova; Tomas Cajthaml (Agriculture)
The use of some organic fertilizers may raise concerns about the transfer of hazardous substances to soil and plants. This study examined the impact of soil amendment with compost and vermicompost derived from sewage sludge and straw pellets in different ratios on the accumulation of pharmaceuticals and personal care products (PPCPs) by hemp (Cannabis sativa L.). The concentrations of fifty different PPCPs were measured in compost-treated soil, and in the roots and above-ground biomass of cannabis grown on the soil. The highest bioaccumulation of PPCPs was recorded in plants from previously unfertilized soils low in organic matter, while the lowest concentrations were measured in soil amended with compost or vermicompost made from straw pellets only, without sewage sludge. The effect of sludge-derived compost and vermicompost application on the absorption of PPCPs was statistically determined by measurements in soil samples, roots and shoots of carbamazepine, cetirizine, lamotrigine, telmisartan, paraxanthine, tramadol, triclosan, and venlafaxine. The above-ground biomass exhibited lower PPCP content than roots, suggesting a potential plant defense mechanism for limiting contaminant translocation. Only tramadol and carbamazepine showed significantly increased content in above-ground biomass.